Chemical composition of essential oil from Semenovia suffruticosa and their antimicrobial’s effects in drinking water - Sardashti, Alireza; Tamandani, Ali (Jordan Journal of Pharmaceutical Sciences, 2021)
This study reports the chemical composition and antibacterial activity of the essential oil from aerial parts of Semenovia suffruticosa (which is endemic to Iran). The essential oil of aerial parts extracted by hydro distillation method and was investigated using GC& GC-MS techniques. The oil yield (w/w %) was 0.77 on dry weight. Sixty components were recognized consists of 84.99 % of total oil .The major components found in the oil: cis-ocimene (19.31%), linalool (9.00), cinnamy valerate(8.19%), α-terpinolene (5.49% ) ,6-amyl-α-pyrone(4.55%) and unknown compounds (1.70 %).The percentage of oxygenated terpenoids and total terpenoids in the essential oil are 22.69 and 61.42 respectively. Antimicrobial effects of this oil were examined according to Agar dilution method. The results of Minimal inhibition Concentration presented, in the following: Staphylococcus aureus (8 μg.mL-1), Salmonella typhi (32 μg.mL-1), Escherichia coli (32 μg.mL-1), Candida albicans(8 μg.mL-1), Aspergillus niger(32 μg.mL-1), shows that the highest dilution of essential oil has been on Candida albicans and the lowest dilution of essential oil that is capable of control on micro-organism, has been pseudomonas aeruginosa . The antimicrobial effects of essential oil have been demonstrated in drinking water using the heterotrophic plat technique. The increase of this essential oil among the samples resulted in decreasing the number of micro-organisms colonies